Some Generalized T-Spherical and Group-Generalized Fuzzy Geometric Aggregation Operators with Application in MADM Problems - Yujuan Chen; Muhammad Munir; Tahir Mahmood; Azmat Hussain; Shouzhen Zeng (Journal of Mathematics)
In this article, the generalized parameter is involved in T-spherical fuzzy set (TSFS), and with the help of this generalized parameter, some generalized geometric aggregation operators for TSFSs are proposed. Then these operators are extended for group-generalized parameter. By using proposed operators, an algorithm is developed for the MADM problem. To check the validity of proposed operators, a numerical example is also investigated. In a comparative analysis, it is discussed that, under some conditions, the proposed work can be reduced to other fuzzy structures. An example is also solved in which it is shown that our proposed technique is superior to the existing technique.